El Excentrico, 1970-05-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
May 20, 1970 [20 de mayo de 1970]. No volume or issue number. Cover has a headshot of Ralph Howard for his election for sheriff.